Communication Analysis of the Political Image of the Demokrat Party on Social Media - Tiara Friska Mauliana; Ahmad Sampurna (UMSU, 2023)
Technology has infiltrated human life in many ways. One of the most common technological developments is social media. Not only for the general public, but also the political world is inseparable from social media in this era. For political actors, social media is a platform to contain positive support. But with the ease of stemming positive images, it cannot be denied that social media can also be a boomerang that can damage their political image at any time. This paper focuses on discussing the Demokrat Party's political communication in shaping its political image, especially on social media platforms. By using a descriptive method, namely taking sources from other literature. In this paper, the use of social media by the Democratic Party will be presented. Furthermore, in terms of the political communication used, it can be concluded that social media also plays an important role as a campaign platform and in building the party's image.